The role of depression, anxiety and illness characteristics on risky sexual behaviour among people with HIV - Chong, Seng Choi; Ibrahim, Normala; Ang, Jin Kiat; Masiran, Ruziana; Tan, Kit Aun; Beatrice, Ng Andrew; Soh, Kwong Yan; Kumar, Suresh (Bentham Science Publishers, 2019)
Background: People living with HIV (PLHIV) have a longer lifespan with treatment and continue to be sexually active. To date, the extent of risky sexual behaviour among local PLHIV and its associated factors were undetermined. Objective: To examine the role of depression, anxiety and illness characteristics on risky sexual behaviour among PLHIV attending care in a Malaysian tertiary reference hospital (N= 406). Methods: It was a cross-sectional study. Subjects were recruited by systematic random sampling. Risky sexual behaviour was determined by using the modified National Youth Risk Behaviour Survey. PHQ-9 and GAD-7 were used to measure the depressive and anxiety symptoms, respectively. Chi-square test was used to examine the association between the variables. Multiple logistic regression was used to examine the predictors of the study. A p value of less than 0.05 was considered significant and odds ratio was used as the measure of risk association. Results: Our study showed that 29.3% had risky sexual behaviour. Meanwhile, 21.9% and 26.4% had depressive and anxiety symptoms, respectively. Risky sexual behaviour was significantly associated with age, religion, education level, duration of HIV diagnosis, depressive and anxiety symptoms. From multivariate logistic regression, duration of HIV diagnosis and anxiety symptoms significantly predicted risky sexual behaviour. Conclusion: This study highlights that a substantial number of PLHIV had risky sexual behaviour and psychological symptoms. It is important for psychological interventions that reduce risky sexual behaviour among PLHIV who attend treatment, especially during the early phase.